PW 1635 Chronic medical conditions and the risk of road traffic crash in older drivers: results from the gazel cohort. (November 2018) - Orriols, Ludivine; Naredo-Turrado, Juan; Contrand, Benjamin; Lafont, Sylviane; Salmi, Louis Rachid; Zins, Marie; Lagarde, Emmanuel
Abstract : The number of elderly drivers is rapidly increasing. Older people have an increased frailty and an associated increase in injury susceptibility. Furthermore, driver's conditions are important factors when assessing fitness to safe driving. The ageing of the population therefore leads to the question of the contribution of chronic medical factors to road traffic crashes involvement among elderly drivers. The GAZEL cohort includes past employees of the electricity and gas French company, who volunteered to participate in a multi-purpose health-related research cohort. Since 1989, participants have been followed up using administrative data and yearly self-administered questionnaires. The study sample consisted in 13 891 participants who were active drivers during the period 2007–2015. Data on road traffic crashes, relevant confounders (age, alcohol consumption, family status and gender) and medical conditions were collected. We will fit a generalized estimating equations model (GEE) after multiple imputation in order to identify medical conditions which are associated with increased odds of road traffic crashes involvement among elderly drivers. To date, this is the largest study of its kind of people aged 60 years or over in France. Prevention could benefit from the evaluation of fitness to drive according to the status of these conditions. However, our study suggests a better understanding of the driving behavior adaptation among older drivers is necessary to apply sensible policies.